Virtual Classes for the Working Mathematician - Battistella, Luca; Carocci, Francesca; Manolache, Cristina (Symmetry, Integrability and Geometry: Methods and Applications, 2020)
This note is intended to be a friendly introduction to virtual classes. We review virtual classes, and we give a number of properties and applications. We also include a new virtual push-forward theorem and many computations of virtual classes in simple examples.